Estudio bibliométrico de la producción científica mundial en nitazoxanida - Martinez-Pulgarin, Dayron F; Muñoz-Urbano, Marcela; Gómez-Suta, Daniela; Sánchez-Duque, Jorge A; Rodriguez-Morales, Alfonso J; Machado-Añba, Jorge Enrique (Revista Médica de Risaralda, 2015)
Estudio